Meet Andrew Jackson - De Kay, Ormonde, 1923-; Barnett, Isa. (New York : Random House, 1967)
An easy-to-read biography of the colorful American general whose victory over the Redcoats at the Battle of New Orleans made him a national hero and aided in helping him become America's seventh President.
Keywords: Jackson, Andrew, 1767 -- 1845 -- Juvenile literature